Effect of resistance exercise on physical fitness, quality of life, and fatigue in patients with cancer: a systematic review - Zhang, Qiuhua; Gao, Yanan; Wang, Wenjun; Zhao, Xiaoguang; Yu, Jiabin; Huang, Huiming (Frontiers in Oncology, 2024)
Objective: The purpose of this study is to conduct a systematic review to assess the effects of different forms of resistance exercises (resistance exercise, resistance combined with aerobic exercise, resistance combined with other exercises) on physical fitness, QOL, and fatigue of cancer patients. Methods: We conducted a systematic review using the Cochrane Handbook for Systematic Reviews of Interventions guidelines. We searched PubMed, Web of Science, and Scopus databases for the studies from the establishment of the database to September 2023. Including randomized controlled trials and clinical trials that evaluated the effects of different resistance exercise on physical fitness, QOL, and fatigue in all cancer patients. Two reviewers independently assessed the quality of all the included studies using the Cochrane Handbook for Systematic Reviews of Interventions and MINORS scale. We divided the intervention into three types: resistance exercise, resistance combined with aerobic exercise, resistance combined with other exercises. Results: In total, 48 studies (3843 participants) met the inclusion criteria. The three exercise intervention forms have significant effects on physical fitness and QOL, but the improvement effect on fatigue is not clear. 34 studies reported significant and beneficial effects of resistance exercise on physical fitness across all types of cancer. 28 studies reported significant or borderline improvement effects of resistance on QOL, and only 10 studies reported significant effects of resistance exercise interventions on fatigue improvement in cancer patients. Conclusions: Whether resistance exercise, resistance combined with aerobic exercise or combination with others, all have a positive effect on improving Fitness and QOL in cancer patients. Resistance exercise has an advantage in improving muscle strength, while combined resistance exercise has an advantage in improving QOL; however, there are no consistent findings in improving fatigue, although low-intensity resistance exercise is effective.